Biochemical Characterization of Metallo-β-Lactamase VIM-11 from a Pseudomonas aeruginosa Clinical Strain - Marchiaro, Patricia (2008)
Fil: Marchiaro, Patricia. Universidad Nacional de Rosario. Departamento de Microbiología; Argentina.